Christian Worker Analogy According to 2 Timothy 2:1-13 and Its Implications for Sunday School Teacher Professionalism - Diana, Ruat; Br. Simamora, Elsi Susanti; Br. Perangin-angin, Darni; Okoi, Ibiang O. (Integritas: Jurnal Teologi, 2023)
This article is conducting research based on the analogy by the Apostle Paul mentioned in 2 Timothy 2:1-13. In the text, Paul makes an analogy of Christian workers in three analogies. This analogy has something to do with the teacher’s professionalism. Therefore the research being done here is divided into two parts, namely the analogy of Christian workers in 2 Timothy 2:1-13 and the second part the implications for the professionalism of Sunday school teachers. The research approach being used includes exegesis research through utilizing Biblical hermeneutic principles and also through utilizing an analysis of implications. The hermeneutic process of the Bible is carried out by analyzing the context and meaning that is found in the text of 2 Timothy 2:1-13. We have used several relevant sources such as books on Bible commentaries and various research reports both in journals and repositories. The implication analysis was carried out after completing the exegesis of 2 Timothy 2:1-13. We have examined the various phenomena that are related to the professionalism of Sunday school teachers and find their correlation to the results of the exegesis already conducted beforehand. The results of the study show that Christian workers by way of analogy in comparison to soldiers, sportsmen, and farmers. The first is the soldier analogy. The soldier analogy explains that the Christian worker is ready to fight on the battlefield to defend his faith in Christ. The second analogy is the sportsman analogy. The sportsman's analogy explains that Christian workers must prepare himself or herself before the competition. In the analogy of sportsmen, Christian workers must be consistent, enterprising, and ready to finish the matches with an enthusiastic spirit. The third analogy is the farmer's analogy. The farmer's analogy explains that Christian workers must be ready to plant the seed of God's Word in everyone's heart. In the farmer's analogy, Christian workers must also be patient and diligent in caring for the seeds of the world that are planted so that these seeds may produce fruit.